Advanced Glycation End Products Upregulate CD40 in Human Retinal Endothelial and Müller Cells: Relevance to Diabetic Retinopathy - Jose-Andres C. Portillo; Amelia Pfaff; Sarah Vos; Matthew Weng; Ram H. Nagaraj; Carlos S. Subauste (Cells, 2024)
CD40 induces pro-inflammatory responses in endothelial and Müller cells and is required for the development of diabetic retinopathy (DR). CD40 is upregulated in these cells in patients with DR. CD40 upregulation is a central feature of CD40-driven inflammatory disorders. What drives CD40 upregulation in the diabetic retina remains unknown. We examined the role of advanced glycation end products (AGEs) in CD40 upregulation in endothelial cells and Müller cells. Human endothelial cells and Müller cells were incubated with unmodified or methylglyoxal (MGO)-modified fibronectin. CD40 expression was assessed by flow cytometry. The expression of ICAM-1 and CCL2 was examined by flow cytometry or ELISA after stimulation with CD154 (CD40 ligand). The expression of carboxymethyl lysine (CML), fibronectin, and laminin as well as CD40 in endothelial and Müller cells from patients with DR was examined by confocal microscopy. Fibronectin modified by MGO upregulated CD40 in endothelial and Müller cells. CD40 upregulation was functionally relevant. MGO-modified fibronectin enhanced CD154-driven upregulation of ICAM-1 and CCL2 in endothelial and Müller cells. Increased CD40 expression in endothelial and Müller cells from patients with DR was associated with increased CML expression in fibronectin and laminin. These findings identify AGEs as inducers of CD40 upregulation in endothelial and Müller cells and enhancers of CD40-dependent pro-inflammatory responses. CD40 upregulation in these cells is associated with higher CML expression in fibronectin and laminin in patients with DR. This study revealed that CD40 and AGEs, two important drivers of DR, are interconnected.